Do responsible fishing areas work? Comparing collective action challenges in three small-scale fisheries in Costa Rica. Issue 1 (April 2019) - Chavez Carrillo, Isis Ivania; Partelow, Stefan; Madrigal-Ballestero, Roger; Schlüter, Achim; Gutierrez-Montes, Isabel
Costa Rica is supporting Marine Areas of Responsible Fishing (AMPRs) to enable small-scale fishing communities to apply for exclusive harvesting and management rights within spatially delimited areas under a co-management policy framework. Communities need to self-organize their own fishing association and develop a fishing management plan (POP) to apply. Seven AMPRs have been established in the Gulf of Nicoya, highlighting Costa Rica's efforts to follow the FAO Small-Scale Fisheries Guidelines, but all face collective action challenges to develop and achieve common goals and implementation. In this article, we conduct a qualitative comparative analysis by applying the Social-Ecological System Framework (SESF) as a tool to identify the social and ecological conditions influencing collective action and co-management in three AMPRs in the Gulf of Nicoya, and we compare the similarities and differences between them. Our findings show that all three AMPRs face collective action challenges for different reasons. Nonetheless, some commonalities exist. Common drivers have motivated collective action in the creation of the AMPRs, including the desire to restrict certain types of fishing gears due to perceptions of resource scarcity and high dependence on local resources. Variables such as monitoring and sanctioning mechanisms, strong leadership and the economic heterogeneity of actors positively influence collective action in management. However, there are also variables hindering collective action, such as mistrust among actors, internal conflicts, lack of governmental support and resource unit mobility. Our findings suggest that AMPRs are a promising and potentially effective governance strategy because they can empower marginalized small-scale fishing communities and bring them into national development processes. However, there is an evident need for more state and local community investment into capacity building for self-organization and deliberation processes that can better enable AMPRs to move beyond "paper parks", and towards being a practically useful governance strategy to showcase Costa Rica's commitment to FAO Small-Scale Fisheries Guidelines. Adapting the AMPR model to fit the social-ecological context of each community is critical for success, despite the perceived similarity between the AMPRs.